Rotary ultrasonic machining of CFRP/Ti stacks using variable feedrate - Cong, W. L.; Pei, Zhijian J.; Deines, Timothy W.; Liu, D. F.; Treadwell, C. (My University, 2013)
Rotary ultrasonic machining (RUM) has been successfully used to drill Ti (titanium and its alloy), CFRP, and CFRP/Ti stacks. In all studies on RUM reported in the literature, feedrate was fixed during each experimental test. It has been shown that low feedrate should be used for RUM of Ti, but RUM of CFRP could be done using feedrate ten times higher. This paper, for the first time, reports a study on RUM of CFRP/Ti stacks using variable feedrate (high feedrate for CFRP and low feedrate for Ti). It also makes comparisons on RUM of CFRP/Ti stacks using fixed and variable feedrate.
Keywords: Polymer-matrix composites; Joints/joining; Machining; CFRP/Ti stacks